STRATEGI DAN KRITERIA LAZISMU UMS MEMBERIKAN BEASISWA TERHADAP MAHASISWA KURANG MAMPU PADA MASA PANDEMI COVID 19 - Riska Amanda Agustina; Yayuli Yayuli (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2021)
This research is entitled "Strategies and Criteria for Lazismu UMS to Provide Scholarships to Underprivileged Students During the 2020/2021 Covid-19 Pandemic. It is raised from the problem "What is the strategy used by Lazismu UMS in managing scholarship funds?" and "What are the criteria for students who deserve a scholarship from Lazismu UMS during the pandemic?". The purpose of this research is to find out what strategies are used by Lazismu UMS in managing scholarship funds and to find out what are the criteria for eligible students to get scholarships from Lazismu UMS. This type of research is descriptive-qualitative field research. The data that the authors collect is from the results of direct interviews and the Lazismu UMS website. There are several strategies for scholarship funds: 1). Do fundraising for each faculty. 2). Diversion of activity funds outside the solo area for handling ums who care about covid-19. The existence of 3 criteria, namely (Really Need, Need, Still Able) from the distribution of these criteria makes it easier to distribute scholarships.